I have something to say : mastering the art of public speaking in an age of disconnection - Bowe, John (2020)
"In eleventh grade, John Bowe's cousin Bill asked a classmate to prom. She said no. Bill responded by moving to the family basement--and staying there for the next forty-three years. But in 1992, at the age of fifty-nine, Bill surprised everyone who knew him: He got married. Bowe learned that Bill credited his turnaround to a non profit club he'd joined called Toastmasters International. Fascinated by the idea that speech training seemed to foster the kind of psychological well-being more commonly sought through expensive psychiatric treatment, and intrigued by the notion that words could serve as medicine-- healing the shy, connecting the disconnected, and mending our frayed social fabric--Bowe sets out to learn for himself what he'd gathered from so many others: When you learn to speak in public, you undergo a profound transformation that has very little to do with standing at a podium. Through his own Toastmasters journey, Bowe learns much more than how to overcome the nervousness associated with giving a speech. He learns that public speaking is really about the audience--it's the art of paying attention. Ultimately, Bowe finds that the key to eloquence, to overcoming shyness, is not mastering one's self or one's fears, but honing one's ability to empathize, pay attention to other people, and connect"--
Active participation -- Yes. You. Can. -- Getting to the point -- You kind of mellow out -- The power zone -- Letting it all hang out -- Facts are silly things -- Seeing is believing -- Find the pizza -- Toward justice and harmony.
Includes bibliographical references (pages 217-218).
Keywords: Bowe, John; Toastmasters International -- Biography; Journalists -- United States -- Biography; Public speaking